Domestic Free-Range Pig Genetic Resources in Southern Africa: Progress and Prospects - Tinyiko Edward Halimani; Obvious Mapiye; Tawanda Marandure; Diedre Januarie; Venancio Edward Imbayarwo-Chikosi; Kennedy Dzama (Diversity, 2020)
Pig genetic resources in Africa originate from different regions and were introduced through several migration pathways. Genetic analysis has shown a strong phylogeographic pattern, with pigs on the eastern parts showing a high frequency of alleles from the Far East while the ones on the western parts show a strong European influence. This highlights the influence of trade routes on the genetic legacy of African pigs. They have, however, since adapted to the local environments to produce unique populations with unique attributes. Most of the pigs are now reared in resource-constrained smallholdings under free-range conditions. They are largely owned by women who spread ownership of the resource through kinship networks. Very little work has been done to characterize, conserve, and sustainably utilize pig genetic resources in Southern Africa. The risk status of the breeds together with population numbers, distribution, and other attributes are largely unknown. This paper proposes several strategies for the sustainable utilization of the pig genetic resources: A market-driven in situ conservation program and two complementary ex situ strategies. In addition, the possibility of community-based breed improvement programs is discussed. It was concluded that genetic characterization of domestic free-range pig populations should be a supreme priority.